Visión geopolítica del ecuador en el período 2006 - 2016: Su influencia en la Seguridad y Defensa. - Lara Tapia, Luis Gavino. (2019)
Geopolitics has been considered as a science by the scientific contributions of the Political Sciences as well as Geography, which undoubtedly have allowed it to define a series of knowledge that has been embodied in theories, laws and principles, put at the service of statesmen and strategists, to whom it provides not only the geographical sense of governing, but also the possibility of including in the analysis of institutions, socio-cultural aspects resulting from processes of social construction in each epoch and in virtue of the current world order, as a reality built in a dynamic way; Therefore, this research intends to make an academic reflection, starting from the analysis of the progress that Geopolitics has had, its validity, its repercussions in Security and Defense, the influence in South America, and in that context, present an approximation to the Ecuadorian geopolitical thought, for which, the study of the geopolitical codes of the country and its influence in the foreign policy of the same has been considered. This work has been traced from a theoretical perspective of constructivism, starting from the deterministic conception of its beginnings, to postmodernist criticism, for which the methodology of discourse analysis has been proposed with a documentary review, through stages of collection of information, analysis and presentation of results, considering the thinking of several authors who, through books, scientific articles and post-graduate work, contributed to the enrichment of this science, in addition, they allowed to find through the analysis of the different theories, which been its progress, validity and / or complementarity, reaching the conclusion that its reflection is in the discourse, the regulations, as well as in the institutions created at a global, regional or national level.